A contribution to knowledge of Dermestidae (Coleoptera) from Kazakhstan with description of one new species - Nakládal, Oto; Háva, Jiří (Zootaxa, 2015)
Research on skin beetles of tugai forests with use of passive window traps was performed in Almaty region in Kazakhstan in 2013. Ctesias (Decemctesias) yuliyae sp. nov. is described, illustrated, and compared with similar species of the genus Ctesias subgenus Decemctesias Háva, 2004. The new species differs by the structure of antennae and male genitalia. Eighteen other dermestid species from Kazakhstan were also recorded in this study.